Glass sealing material for medium-temperature solid oxide fuel cell and preparation method of glass sealing material
By optimizing the composition of glass components and melting process, glass sealing materials with high thermal stability and chemical compatibility were prepared, which solved the problem of insufficient performance of traditional glass sealing materials under high temperature conditions, and improved the stability of SOFC systems and efficiency.
Patent Information
- Application Number
- CN202411570737.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-02-11
AI Technical Summary
Traditional glass sealing materials are difficult to meet the performance requirements of solid oxide fuel cells under high-temperature oxidation and reducing service conditions, and there are problems of poor thermal performance and high brittleness, resulting in insufficient sealing effect and stability.
By optimizing the composition and melting process of glass components, glass sealing materials using SiO2, B2O3, Al2O3, SrO, CaO, Na2O and additives such as La2O3, Y2O3, Nd2O3, WO3, etc., combined with wet grinding method and optimized smelting parameters, Glass sealing materials with high thermal stability and chemical compatibility were prepared.
It improves the thermal stability and airtightness of glass sealing materials, enhances its performance under high temperature conditions, reduces the gas leakage rate and maintenance cost of SOFC systems, and promotes the further development and application of SOFC technology.
Smart Images

Figure CN119409419A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of solid oxide fuel cell materials, and in particular to a glass sealing material for medium-temperature solid oxide fuel cells and a preparation method thereof. Background Art
[0002] Solid Oxide Fuel Cell (SOFC) and Solid Oxide Electrolysis Cell (SOEC) technologies have attracted much attention due to their potential in energy conversion and energy storage. Their uniqueness lies in their ability to directly convert the chemical energy of various fuels into electrical energy with high conversion efficiency, thus presenting a wide range of application prospects.
[0003] The high-efficiency conversion characteristics of SOFC / SOEC technology make it a key link in fuel cell technology. According to research, its electric-thermal cogeneration efficiency can be as high as 80% or more, and its power generation efficiency can reach 40-60%, which provides great potential for improving energy utilization efficiency. In addition, SOFC / SOEC technology does not involve the combustion process, so there is no harmful gas emission, which meets the requirements of environmental protection and sustainable development. The combination of this technology with renewable energy provides new impetus for its application and can effectively promote the development of clean energy. However, SOFC / SOEC technology still faces a series of technical challenges, among which the sealing technology problem is particularly prominent. Especially in harsh environments such as high temperature, high pressure, and corrosive atmosphere, the seals in SOFC / SOEC equipment must have excellent high temperature resistance, corrosion resistance and mechanical stability. Traditional glass sealing materials have poor thermal properties and high brittleness, and it is difficult to meet the performance requirements of battery power under high-temperature oxidation and reduction service conditions. Therefore, finding new high-performance sealing materials and optimizing the sealing process have become one of the current research focuses. In summary, the development prospects of solid oxide fuel cells and electrolyzers are broad, but to realize their application in engineering practice, a series of technical challenges still need to be overcome.
[0004] In order to solve the above problems, researchers have adopted the method of optimizing glass composition or adding strengthening phase to effectively improve the mechanical properties and sealing effect of sealing materials. CN104505527B discloses a medium-temperature flat-plate solid oxide fuel cell stack seal and its preparation method. By adding Al2O3 ceramic strengthening phase to the sealing glass powder, the mechanical properties of the glass sealing material are improved and the airtightness of the SOFC stack is effectively improved. CN104703936A discloses a glass composition for use as a sealant. The glass component includes 35~70mol% CaO, 5~45mol% ZnO, 5~50mol% B2O3, 1~45mol% SiO2 and 1mol% or less of Ba, Na and Sr elements. The glass sealing material has the advantages of good adhesion and high matching of thermal expansion coefficient.
[0005] In addition, in order to improve the problem of insufficient thermal stability of sealing glass, other patents such as CN114436533B and CN106277794B adopt the strategy of adding rare earth or lanthanide oxides, which effectively solves the problems of poor thermal stability and uncontrollable viscosity of sealing glass. In addition, Anjana et al. (Synthesis and characterization of 50BaO-(5-x)Al2O3-xR2O3-30B2O3-15SiO2(R=Nd, Gd)glass-ceramics) improved the integrity of the network structure of sealing glass by changing the type and content of Nd and Gd rare earth oxides, and the thermal stability (ΔT) was significantly improved. In particular, when the content of Nd and Gd was increased to 5mol%, the ΔT value reached 177°C. This further proves the advantages of rare earth oxides and lanthanide metal oxides in improving the thermal stability of glass.
[0006] CN106277794B discloses a glass-glass composite sealing material, a preparation method and an application thereof, and proposes a "low softening point + high softening point" matching strategy, which can flexibly adjust the thermal properties and sealing effect of the sealing material, and has the characteristics of low transition temperature and good chemical compatibility with other components.
[0007] Despite this, there are still obvious deficiencies in the glass melting process, especially for glasses containing a large amount of volatile oxides (B2O3, Na2O, etc.), such as the glass sealing materials in CN104703936A and CN106277794B. The conventional melting process can easily lead to serious volatilization of oxides. Ultimately, the glass component content is difficult to control, and the thermal stability and sealing effect are poor. There are few related reports and the melting difficulty is relatively high, which puts higher requirements on the melting process of this type of glass.
[0008] In summary, although the existing patents have made some progress in glass sealing effects, the problems of insufficient thermal stability of sealing glass and difficult control of component content remain to be solved. Therefore, this patent proposes a glass sealing material for medium-temperature solid oxide fuel cells and a preparation method thereof, which is expected to improve the above problems by optimizing glass components and improving the melting process. Summary of the invention
[0009] The object of the present invention is to provide a glass sealing material for medium-temperature solid oxide fuel cells and a preparation method thereof, so as to solve the problems in the background technology.
[0010] To achieve the above object, the present invention provides a method for preparing a glass sealing material for a medium-temperature solid oxide fuel cell, comprising the following steps: (1) Calculate and weigh SiO2, B2O3, Al2O3, SrCO3, CaCO3, Na2CO3 and additive raw material powders according to molar percentage, put them into an agate ball mill, use anhydrous ethanol as a dispersant, set the wet milling process parameters of the planetary ball mill, and then perform wet milling, drying and sieving; (2) placing an alumina crucible in a melting furnace and burning it in an empty state, then adding the mixed raw material powder into the alumina crucible, taking out the alumina crucible after melting, placing the glass liquid in deionized water at 25° C. for quenching, obtaining an original glass frit, and drying it; (3) Add the glass frit into an agate ball mill, use anhydrous ethanol as a dispersant, set the process parameters of the wet grinding method of the planetary ball mill, and then perform wet grinding. After drying again, sieve to obtain glass sealing material powder.
[0011] Preferably, in step (1), the wet grinding process parameters are: ball milling speed 500 rpm; ball milling time 2 h; drying through a 300 mesh sieve.
[0012] Preferably, in step (1), the mass ratio of agate grinding balls, anhydrous ethanol and raw material powder is 5:5:2.
[0013] Preferably, in step (2), the temperature is raised to 1000°C at a heating rate of 10°C / min, and then the temperature is raised to 1200°C at a heating rate of 5°C / min, and the temperature is kept at this temperature for 10 to 60 minutes.
[0014] Preferably, in step (2), the smelting parameters are: heating rate of 3-5°C / min, heating to 1400-1600°C and melting for 1-4h.
[0015] Preferably, in step (3), the mass ratio of agate grinding balls, anhydrous ethanol and glass frit is (4-6): (4-6): (1-3).
[0016] Preferably, in step (3), the wet milling process parameters are: ball milling speed 300-500 rpm; ball milling time 6-12 h.
[0017] Preferably, in step (3), the glass sealing material powder is dried and passed through a 300-400 mesh sieve, and the particle size D 50 2~20μm.
[0018] The present invention also provides a glass sealing material for medium-temperature solid oxide fuel cells prepared by the above preparation method.
[0019] Preferably, the glass sealing material contains SiO2 35~60mol%, B2O3 2~10mol%, Al2O3 0~4mol%, SrO 10~35mol%, CaO 10~25mol%, Na2O 0~10mol% and additive 0~5mol%; wherein the additive is any one of La2O3, Y2O3, Nd2O3, WO3.
[0020] Therefore, the present invention provides a glass sealing material for medium-temperature solid oxide fuel cells and a preparation method thereof. By designing the composition of the sealing material, a matching relationship between the glass composition and the thermal performance is established, and a sealing material with strong thermal stability and good chemical compatibility with other battery components is developed. The stability of the SOFC stack within the operating temperature range is effectively improved, and it can withstand thermal stress and thermal cycle shock under high-temperature service conditions. In addition, by optimizing the melting process of the sealing material, the degree of burning of components such as B2O3 and Na2O is reduced, and the composition stability and thermal stability of the sealing material are improved. Ultimately, the airtightness and reliability of the glass sealing material are synergistically improved, and the gas leakage rate and maintenance cost of the SOFC system are reduced, thereby promoting the further development and application of SOFC technology.
[0021] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 The microscopic morphology of the sealing glass powder obtained in Example 1 of the present invention; Figure 2 This is the X-ray diffraction (XRD) result of the sealing glass powder of Example 1 of the present invention; Figure 3 The test result of the coefficient of thermal expansion (CTE) of the sealing glass in Example 1 of the present invention is shown; Figure 4 The test results of thermogravimetric differential scanning calorimetry (DSC) of the sealing glass powder in Example 1 of the present invention are as follows; Figure 5The test results of thermogravimetric differential scanning calorimetry (DSC) of the sealing glass powder of Example 2 of the present invention are as follows; Figure 6 This is the test result of thermogravimetric differential scanning calorimetry (DSC) of the sealing glass powder in Example 3 of the present invention. DETAILED DESCRIPTION
[0023] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention. Any other changes, modifications, substitutions, combinations, and simplifications made without violating the spirit and principle of the present invention should all be equivalent replacement methods and are included in the protection scope of the present invention. In addition, it should be understood that after reading the content of the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined by the claims attached to this application, and all belong to the scope of protection of the present invention.
[0024] Reference to "embodiment" herein means that the specific features, structures or characteristics described in conjunction with the embodiment may be included in at least one embodiment of the present application. The term "embodiment" appearing in various places in the specification does not necessarily refer to the same embodiment, nor does it particularly limit its independence or association with other embodiments. In principle, in the present application, as long as there is no technical contradiction or conflict, the various technical features mentioned in the embodiments can be combined in any way to form a corresponding implementable technical solution.
[0025] Unless otherwise defined, the technical terms used in this document have the same meanings as those generally understood by those skilled in the art to which this application belongs; the use of relevant terms in this document is only for describing specific embodiments and is not intended to limit this application.
[0026] Unless otherwise specified in the present invention, the reagents, instruments, and equipment used are those commonly used by technicians in this field.
[0027] Embodiment 1 This embodiment provides a method for preparing a glass sealing material having a composition of 44SiO2-10B2O3-4Al2O3-25SrO-11CaO-6Na2O. The sealing glass material is used for a medium-temperature solid oxide fuel cell. The steps for preparing the sealing glass material are as follows: (1) Calculate and weigh SiO2, B2O3, Al2O3, SrCO3, CaCO3, and Na2CO3 raw material powders according to the corresponding molar percentages, with a total weight of 20 g, and put them into an agate ball mill. Use anhydrous ethanol as a dispersant and wet-mix the raw material powders at a speed of 500 rpm for 120 min at a mass ratio of agate grinding balls: anhydrous ethanol: raw material powders of 5:5:2. Then dry and pass through a 300-mesh sieve.
[0028] Among them, the actual weighed amount of B2O3 raw material is 1.1 times the designed amount, and the actual weighed amount of Na2CO3 raw material is 1.03 times the designed amount.
[0029] (2) Preheat the alumina crucible in a melting furnace, first heat it to 1000°C at a heating rate of 10°C / min, then heat it to 1200°C at a heating rate of 5°C / min, and keep it warm for 60 minutes.
[0030] The mixed raw material powder was added into an empty alumina crucible, and after melting at 1550°C for 60 minutes, the crucible was taken out of the furnace and the glass liquid was quenched in deionized water at 25°C to obtain the original glass frit, which was then dried.
[0031] (3) Add the glass frit into an agate ball mill, use anhydrous ethanol as a dispersant, wet mix the raw material powder at a mass ratio of agate ball: anhydrous ethanol: glass frit of 5:5:2, and a speed of 500 rpm for 8 hours, and then dry it through a 400 mesh sieve. The particle size of the obtained glass sealing material powder is D 50 Around 5μm.
[0032] The glass sealing material prepared in this embodiment was tested, and the test results are as follows: Figure 1-4 shown.
[0033] Depend on Figure 1 The microscopic morphology of the sealing glass powder shows that the particle size D of the glass sealing powder prepared in this embodiment is 50 It is about 4.2μm.
[0034] Depend on Figure 2 From the diffraction pattern of the sealing glass powder, it can be seen that the glass obtained in this example has typical amorphous diffuse scattering peak characteristics. When 2θ is about 28° and 45°, there are two obvious broad peaks, and no crystal diffraction peaks are found in the characteristic spectrum. Figure 2 The XRD diffraction results basically indicate that the glass obtained in this example is completely amorphous glass.
[0035] Depend on Figure 3 From the elongation curve in the figure, we know that the thermal expansion coefficient of the sealing glass is 9.8×10 -6 K-1 , which meets the requirements of SOFC stack for the thermal expansion coefficient of sealing glass.
[0036] Depend on Figure 4 The DSC curve shows that during the test, two exothermic peaks appeared, especially the first exothermic peak with a stronger intensity, and the onset crystallization temperature (T c1 ) and peak crystallizationtemperature (T p1 ) are 870℃ and 904℃ respectively. As the test temperature increases, the second exothermic peak crystallization temperature parameter is 991℃ (T c2 ) and 1008℃ (T p2 ). Moreover, it is found from the DSC curve that the glass transition temperature (T g ) is 660°C. Based on the above results, it can be calculated that the difference between the crystallization peak temperature and the glass transition temperature of the glass is as high as 210°C, that is, the thermal stability (ΔT=210°C), indicating that the sealing glass has a certain thermal stability.
[0037] Embodiment 2 This embodiment provides a method for preparing a glass sealing material having a composition of 44SiO2-8B2O3-2Al2O3-25SrO-11CaO-10Na2O. The sealing glass material is used for a medium-temperature solid oxide fuel cell. The steps for preparing the sealing glass material are as follows: (1) Calculate and weigh SiO2, B2O3, Al2O3, SrCO3, CaCO3, and Na2CO3 raw material powders according to the corresponding molar percentages, with a total weight of 20 g, and put them into an agate ball mill. Use anhydrous ethanol as a dispersant and wet-mix the raw material powders at a speed of 500 rpm for 120 min at a mass ratio of agate grinding balls: anhydrous ethanol: raw material powders of 5:5:2. Then dry and pass through a 300-mesh sieve.
[0038] Among them, the actual weighed amount of B2O3 raw material is 1.1 times the designed amount, and the actual weighed amount of Na2CO3 raw material is 1.03 times the designed amount.
[0039] (2) Preheat the alumina crucible in a melting furnace, first heat it to 1000°C at a heating rate of 10°C / min, then heat it to 1200°C at a heating rate of 5°C / min, and keep it warm for 60 minutes.
[0040] The mixed raw material powder was added into an empty alumina crucible, and after melting at 1550°C for 60 minutes, the crucible was taken out of the furnace and the glass liquid was quenched in deionized water at 25°C to obtain the original glass frit, which was then dried.
[0041] (3) Add glass frit into an agate ball mill, use anhydrous ethanol as a dispersant, wet-mix the raw material powder at a speed of 500 rpm at a mass ratio of agate grinding ball: anhydrous ethanol: glass frit of 5:5:2 for 8 h, and then dry and pass through a 400-mesh sieve.
[0042] The glass sealing material prepared in this embodiment was tested, and the DSC test results are as follows: Figure 5 As shown. Figure 5 The DSC curve shows that during the test, two exothermic peaks still appeared, especially the first exothermic peak with a stronger intensity. c1 ) and peak crystallization temperature (T p1 ) are 809℃ and 855℃ respectively. As the test temperature increases, the second exothermic peak crystallization temperature parameter is 943℃ (T c2 ) and 1004℃ (T p2 ). Moreover, it is found from the DSC curve that the glass transition temperature (T g ) is 566°C. Based on the above results, the T of the glass can be calculated. c1 Temperature and T g The temperature difference is 243°C, which is the thermal stability (ΔT=243°C). This shows that the thermal stability of the sealing glass has been effectively improved by optimizing the glass composition and adjusting the glass network structure.
[0043] Embodiment 3 This embodiment provides a method for preparing a glass sealing material with a new composition, the composition of which is (100-x)(44SiO2-8B2O3-2Al2O3-25SrO-11CaO-10Na2O)-xWO3, x=3mol%. The sealing glass material is used for medium-temperature solid oxide fuel cells, and the preparation steps of the sealing glass material are as follows: (1) Calculate and weigh the raw material powders of SiO2, B2O3, Al2O3, SrCO3, CaCO3, Na2CO3, and WO3 according to the corresponding molar percentages, with a total weight of 20 g, put them into an agate ball mill, use anhydrous ethanol as a dispersant, and wet-mix the raw material powders at a speed of 500 rpm for 120 min at a mass ratio of agate grinding balls: anhydrous ethanol: raw material powders of 5:5:2, and then dry them through a 300-mesh sieve.
[0044] Among them, the actual weighed amount of B2O3 raw material is 1.1 times the designed amount, and the actual weighed amount of Na2CO3 raw material is 1.03 times the designed amount.
[0045] (2) Preheat the alumina crucible in a melting furnace, first heat it to 1000°C at a heating rate of 10°C / min, then heat it to 1200°C at a heating rate of 5°C / min, and keep it warm for 60 minutes.
[0046] The mixed raw material powder was added into an empty alumina crucible, and after melting at 1550°C for 60 minutes, the crucible was taken out of the furnace and the glass liquid was quenched in deionized water at 25°C to obtain the original glass frit, which was then dried.
[0047] (3) Add glass frit into an agate ball mill, use anhydrous ethanol as a dispersant, wet-mix the raw material powder at a speed of 500 rpm at a mass ratio of agate grinding ball: anhydrous ethanol: glass frit of 5:5:2 for 8 h, and then dry and pass through a 400-mesh sieve.
[0048] The glass sealing material prepared in this embodiment was tested, and the DSC test results are as follows: Figure 6 As shown. Figure 6 The DSC curve shows that during the test, two exothermic peaks still appear, especially the first exothermic peak has a stronger intensity, while the second exothermic peak has a lower intensity. c1 ) and peak crystallizationtemperature (T p1 ) are 870℃ and 931℃ respectively. As the test temperature increases, the crystallization temperature parameter of the second exothermic peak is 1014℃ (T c2 ) and 1045℃ (T p2 ). Moreover, it is found from the DSC curve that the glass transition temperature (T g ) is 554°C. Based on the above results, the T of the glass can be calculated. c1 Temperature and T g The temperature difference is 316°C, which is the thermal stability (ΔT=316°C). This shows that by adding WO3 additives, the integrity of the glass network is further strengthened and the thermal stability of the sealing glass is greatly improved.
[0049] In summary, the present invention improves the problem of poor thermal stability of sealing glass by adjusting the composition and content of glass components and optimizing the glass melting process. The glass sealing material obtained through this example meets the sealing requirements of medium-temperature solid oxide fuel cells, which is beneficial to improving the long-term service performance of solid oxide fuel cell stacks.
[0050] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.
Claims
1. A method for preparing a glass sealing material for a medium-temperature solid oxide fuel cell, characterized in that: The following steps are involved: (1) Calculate and weigh SiO2, B2O3, Al2O3, SrCO3, CaCO3, Na2CO3 and additive raw material powders according to molar percentage, put them into an agate ball mill, use anhydrous ethanol as a dispersant, set the wet milling process parameters of the planetary ball mill, and then perform wet milling, drying and sieving; (2) placing an alumina crucible in a melting furnace and burning it in an empty state, then adding the mixed raw material powder into the alumina crucible, taking out the alumina crucible after melting, placing the glass liquid in deionized water at 25° C. for quenching, obtaining an original glass frit, and drying it; (3) Add the glass frit into an agate ball mill, use anhydrous ethanol as a dispersant, set the process parameters of the wet grinding method of the planetary ball mill, and then perform wet grinding. After drying again, sieve to obtain glass sealing material powder.
2. The method for preparing a glass sealing material for a medium-temperature solid oxide fuel cell according to claim 1, characterized in that: In step (1), the wet grinding process parameters are: ball milling speed 500 rpm; ball milling time 2 h; drying through a 300-mesh sieve.
3. The method for preparing a glass sealing material for a medium-temperature solid oxide fuel cell according to claim 1, characterized in that: In step (1), the mass ratio of agate grinding balls, anhydrous ethanol and raw material powder is 5:5:
2.
4. The method for preparing a glass sealing material for a medium-temperature solid oxide fuel cell according to claim 1, characterized in that: In step (2), the temperature is increased to 1000°C at a heating rate of 10°C / min, and then increased to 1200°C at a heating rate of 5°C / min, and kept at this temperature for 10 to 60 minutes.
5. The method for preparing a glass sealing material for a medium-temperature solid oxide fuel cell according to claim 1, characterized in that: In step (2), the smelting parameters are: heating rate of 3-5°C / min, heating to 1400-1600°C and melting for 1-4h.
6. The method for preparing a glass sealing material for a medium-temperature solid oxide fuel cell according to claim 1, characterized in that: In step (3), the mass ratio of agate grinding balls, anhydrous ethanol and glass frit is (4-6): (4-6): (1-3).
7. The method for preparing a glass sealing material for a medium-temperature solid oxide fuel cell according to claim 1, characterized in that: In step (3), the wet milling process parameters are: ball milling speed 300-500 rpm; ball milling time 6-12 h.
8. The method for preparing a glass sealing material for a medium-temperature solid oxide fuel cell according to claim 1, characterized in that: In step (3), the glass sealing material powder is dried and passed through a 300-400 mesh sieve, and the particle size D 50 2~20μm.
9. A glass sealing material for medium-temperature solid oxide fuel cells, characterized in that: The glass sealing material is prepared by the preparation method according to any one of claims 1 to 8.
10. A glass sealing material for medium-temperature solid oxide fuel cells according to claim 9, characterized in that: The glass sealing material comprises SiO2 35-60 mol%, B2O3 2-10 mol%, Al2O3 0-4 mol%, SrO 10-35 mol%, CaO 10-25 mol%, Na2O 0-10 mol% and an additive 0-5 mol%; wherein the additive is any one of La2O3, Y2O3, Nd2O3 and WO3.
Citation Information
Patent Citations
A medium-temperature flat-plate solid oxide fuel cell stack sealant and its preparation method
CN104505527B
Glass composition for the use as a sealant
CN104703936A
Glass-glass composite sealing materials, their preparation methods and applications
CN106277794B
A composite sealing material for solid oxide fuel cells, its preparation method and application
CN114436533B